PENDEKATAN SAINTIFIK DALAM UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA: Penelitian Eksperimen - Dicky Kurnia; Hendro Prasetyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of students’ mathematical understanding because most students find it very difficult to quickly absorb and understand mathematics subjects. In addition, students learning mathematics is not yet meaningful, so students’ understanding of concepts is very weak. The implementation of the Merdeka curriculum in learning with a scientific approach is a learning process that is designed in such a way that students actively construct concepts, laws or principles as well as organize learning experiences in a logical sequence including the learning process: 1) observing; 2) inquiring; 3) collecting information/trying; 4) reasoning/associating; and 5) communicate. This study aims to find out whether there is a difference in the improvement of mathematical comprehension skills of students in the experimental class to the control class, and the attitude of students towards mathematics learning to use a scientific approach. The research method used is the experimental Quasee method with a random, pre-test, post-test design. The subjects in this study were 42 people in the experimental and control class of grade VII students of State Junior High School in Cianjur district. The results of the research obtained in the form of pre-test scores and gain index scores were then processed by the statistical method of testing the difference between two averages. The results showed that there was a difference in the improvement of mathematical comprehension skills of students in the experimental class and the control class. The improvement of mathematical comprehension skills of students who received learning with a scientific approach was better than students who received conventional learning. Students’ attitudes towards mathematics learning with a scientific approach are mostly positive, this can be seen from the scale of students’ attitudes.